An Analysis of intra-sentential switching used by a youtuber: Rachel Goddard - Merry Rullyanti; Eli Diana; Tommi Pungkaswani; Meli Indriani (Literary Criticism, 2020)
Code switching can be produced by bilingual users including a Youtuber. The researcher analyzed the switching by a bilingual Youtuber namely Rachel Goddard. Within the title of “An Analysis of Intra - Sentential Switching Used by a Youtuber: Rachel Goddard”, the discussion of this research deals with the number of utterances. The objectives of this research are to find out types of word included as intra-sentential switching used by Rachel Goddard, the most frequently occurring word included as intra-sentential switching used by Rachel Goddard, and the meaning of the word frequently used by Rachel Goddard included as intra-sentential switching. This research was designed to use descriptive qualitative method. This research was carried out by taking steps to collect data, classify data, analyze data, and make conclusions. The data analysis technique that was used is based on Spradley’s theory. The researcher found 9 types of words appeared in intra-sentential switching used by Rachel Goddard in her selected YouTube videos. They are Noun, Adjective, Conjunction, Adverb, Verb, Exclamation, Preposition, Numeral, and Determiner. There are 772 nouns found in this research. The percentage is 58.08 %. It is the highest value of all. There is only 1 determiner found in this research. The percentage is 0.07 %. It is the lowest value of all. It was also found that there are 1327 data that have denotative meanings and there are 2 data that have connotative meanings. It was analyzed that Rachel Goddard used English words within a clause or sentence in Bahasa Indonesia. The results also show that the kinds of meaning found are mostly included in denotative meaning instead of connotative meaning. Besides that, the videos themselves show the phenomenon of bilingualism. It is hoped that the results will be useful for the development of linguistics especially in English letters or Sociolinguistics Keyword: Sociolinguistics, code switching, Rachel Goddard, word class, meanings